Transforming Distance Learning: New Assessment Methods Impact on Student Success in First-year Public Administration at Free Stat (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
This qualitative case study investigates the impact of revised assessment practices on student success in the first-year online module, Public Administration and Management Theories (EPAM1514), at the University of the Free State (UFS). Historically delivered in a traditional face-to-face format, the transition to online learning presented challenges, particularly in providing timely feedback on assessments. Guided by the theoretical frameworks of constructive alignment and Taylor’s principles, this study explores how aligning learning outcomes, teaching activities, and assessment strategies can improve student success in an online environment. The research employed a qualitative desktop analysis, utilising document analysis and descriptive methods to analyse course documents, assessments, and student performance data. The findings indicate that aligning assessment practices with these principles positively impacts student success, primarily by enabling formative assessments and timely feedback. This approach empowers students to monitor their progress and take ownership of their learning. The study concludes that adapting assessment practices is crucial for enhancing student success in distance learning and emphasises the need for continuous evaluation to maintain alignment with learning outcomes. This research offers valuable insights for both educators and institutions aiming to optimise student learning and performance in online environments.
Keywords: Changing assessment practices; constructive alignment; public administration and management; student success; Taylor's principles